Monogenic mimics of Behçet's disease in the young. (30th January 2019) - Papadopoulou, C; Omoyinmi, E; Standing, A; Pain, C E; Booth, C; D'Arco, F; Gilmour, K; Buckland, M; Eleftheriou, D; Brogan, P A
Abstract: Objectives: Monogenic autoinflammatory disorders (AID) and primary immunodeficiencies can present early in life with features that may be mistaken for Behçet's disease (BD). We aimed to retrospectively describe the clinical and laboratory features of 11 paediatric cases referred for suspected BD who turned out to have an alternative, monogenic disease mimicking BD. Methods: Retrospective, paediatric BD specialist multicentre case series. Next generation sequencing (NGS) or conventional candidate gene screening approaches were utilized, facilitated in some cases by functional assays. Results: Eleven children referred with suspected BD underwent genetic screening because of atypical BD features, and/or presentation before age 5 years. Eight patients (73%) were Caucasian, two were Pakistani and one was Turkish; 55% were female. A positive family history of BD was reported in 54% cases. The median age of disease onset was 0.6 (range 0.2–2.3) years. All had systemic inflammation and oral ulceration; 5/11 had genital ulceration; 3/11 had ocular involvement; and 9/11 had cutaneous manifestations. Nine/11 had known disease-causing genetic mutations in: TNFAIP3 ( n = 2), WDR1 ( n = 2), NCF1, AP1S3, LYN, MEFV and GLA . The remaining two cases each had novel variants in STAT1 and TNFRSF1A. Conclusion: Rare monogenic diseases can mimic BD, particularly when presenting early in life. These observations are now informing a strategy to explore screening for genetic mimics of BD in a UK cohort of children and adults to better understand the proportion of UK BD patients who may in fact have an underlying monogenetic diagnosis.